Unlocking the potential of Embedded Analytics : Exploring the drivers of user behaviour and attitudes - Lhuilier, Victor (My University, 2023)
In recent years, the predominant focus of organisations lied on automating business processes and augmenting productivity using ERP, SCM and CRM solutions. Nonetheless, to maintain competitiveness in the future, organisations must now surpass process automation by embedding them with greater intelligence through the integration of analytics into their processes and business application. Cutting-edge technologies like HTAP have facilitated the convergence of operational and informational environment leading to the creation of a new technology: embedded analytics. Embedded analytics offers relevant and timely insights directly within the context of an application, reducing the need for users to switch between multiple tools or interfaces. Despite its rising popularity, research embedded analytics adoption is still inexistant. The thesis extended the UTAUT to explore factors influencing embedded analytics adoption in organisational contexts. The results indicated that performance expectancy, social influence and facilitating conditions are the primary drivers of embedded analytics adoption. It suggests that organisations and researchers should focus on enhancing performance expectancy by emphasising the usefulness and benefits of embedded analytics, leveraging social influence to promote adoption through influential figures and social norms, and providing facilitating conditions such as resources and support to remove barriers to adoption. Moreover, the findings show that company resources such as UX design, data quality and company mandate strengthen the aforementioned relationships.
Keywords: Embedded Analytics, UTAUT, user adoption, PLS-SEM